Siergiej Paradżanow – reżyser kina ukraińskiego - Wojnicka, Joanna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article presents the films Sergei Parajanov made at the Kiev studio between 1955–1962: Andriesh, The First Lad, Ukrainian Rhapsody, Flower on the Stone and documentaries: Dumka, Golden Hands, Natalya Ushvij. The author focuses on the context of making films and their incorporation into the traditional conventions of Soviet cinema, as well as presenting the sources of the director’s interest in Ukrainian culture.